Changes in excess mortality among adults with diabetes-related end-stage kidney disease: a comparison between the USA and Australia. Issue 10 (1st November 2021) - Harding, Jessica L; Morton, Jedidiah I; Shaw, Jonathan E; Patzer, Rachel E; McDonald, Stephen P; Magliano, Dianna J
ABSTRACT: Background: The number of people with diabetes-related end-stage kidney disease (ESKD-DM) has doubled in the last two decades. We examined changes in excess mortality for people with ESKD-DM in the USA and Australia. Methods: In this retrospective cohort study, we included adults (ages 20–84 years) receiving renal replacement therapy (RRT) for ESKD-DM in the USA ( n = 1 178 860 from the United States Renal Data System, 2002–17) and Australia ( n = 10 381 from the Australia and New Zealand Dialysis and Transplant Registry, 2002–13). ESKD-DM was defined as those with diagnosed diabetes at time of RRT initiation and mortality status was captured from national death registries. Annual standardized mortality ratios (SMR) were stratified by treatment modality, and age, sex and race (USA only). Trends were assessed using join point regression and annual percent change (APC) was reported. Results: Overall, in the dialysis population SMR decreased from 2006 to 2014 in the USA (from 12.0 to 10.1; APC −2.1) and from 2002 to 2013 in Australia (from 12.0 to 9.4; APC −3.4). In the transplant population, SMR decreased from 6.2 to 4.0 from 2002 to 2013 in the USA, and did not significantly change from 2002 to 2013 in Australia. By subgroup, excess mortality was higher in women (versus men), younger (versus older) adults, dialysis (versus transplant) patients, and in Asian or Pacific Islanders and American Indian or Alaskan Natives (AI/AN) (versus Whites and Blacks). SMRs declined similarly across all subgroups excluding AI/AN (USA) and transplant patients (Australia), where relative declines were smaller. Conclusions: Excess mortality for people with ESKD-DM treated with dialysis or transplant has decreased in the USA and Australia, but progress has stalled from ∼2013 in the USA. Nevertheless, mortality remains more than nine times higher in ESKD-DM versus the general population, with important variations by subgroups. Given the increasing burden of diabetes in the population, a focus on reducing excess mortality risk in the ESKD-DM population is needed. Graphical Abstract: